2000
DOI: 10.1046/j.1467-0658.2000.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the efficacy of antipyretic drugs in the prevention of febrile seizure recurrence

Abstract: Objective To estimate the potential preventive effect of antipyretic drugs on the recurrence of febrile seizures (FS). Design An experimental and a descriptive patient series, both prospectively followed, were combined in this study. Setting/participants Children who visited the outpatient department of the Sophia Children’s Hospital because of a FS experienced between the age of 10 and 36 months. Intervention A treatment group of 109 children was offered treatment with ibuprofen or acetaminophen syrup during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, nurses thought that fever should always be treated and even considered waking a sleeping child to give them antipyretics. This was probably related to the belief that antipyretics could prevent febrile seizures, which is an idea that still remains within the medical community , despite lack of support from the evidence .…”
Section: Discussionmentioning
confidence: 99%
“…However, nurses thought that fever should always be treated and even considered waking a sleeping child to give them antipyretics. This was probably related to the belief that antipyretics could prevent febrile seizures, which is an idea that still remains within the medical community , despite lack of support from the evidence .…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence suggests that controlling fever rarely, if ever, prevents initial or recurrent febrile convulsions (Uhari et al. 1995, Baumann 1999, van Esch et al. 2000, Rantala et al.…”
Section: Antipyretic Therapymentioning
confidence: 99%
“…Ibuprofen showed a stronger fever reducing effect as compared to acetaminophen; however, both have been shown to be safe and effective antipyretic drugs in the treatment of fever in children; and are safely administered for comfort during periods of illness. Furthermore, this study (Esch et al, 2000) identified a lack of evidence that antipyretics reduced the incidence of febrile seizures.…”
Section: Pharmacological Treatmentmentioning
confidence: 87%
“…A previous study (Esch et al , 2000), examined ibuprofen versus acetaminophen. The objective was to estimate the potential preventive effect of antipyretics on the recurrence of febrile seizures.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation